2019
DOI: 10.1136/bjophthalmol-2018-313294
|View full text |Cite
|
Sign up to set email alerts
|

Association of visual acuity with educational outcomes: a prospective cohort study

Abstract: Background/aimTo quantify the impact of baseline presenting visual acuity (VA), refractive error and spectacles wear on subsequent academic performance among Chinese middle school children.MethodsA prospective, longitudinal, school-based study on grade 7 Chinese children (age, mean±SD, 12.7±0.5 years, range=11.1–15.9) at four randomly selected middle schools in Anyang, China. Comprehensive eye examinations including cycloplegic autorefraction were performed at baseline, and information on demographic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 24 publications
6
28
0
3
Order By: Relevance
“…Also, the percentage of children that get tired while reading, suffer from headaches, feel that their eyes cry or itch when they read, need to follow the text with their finger, or even get confused or miss words when reading, is lower in the group of children with good academic performance. These results are aligned with other studies carried out in different countries, such as that published by Jan et al, which concluded that better visual acuity is related to higher academic performance in a cohort of children aged between 11 and 16 in China [17]. Regarding reading, Goldstand et al demonstrated in 2006, in 71 seventh grade children, how nonproficient readers had significantly poorer academic performance and vision-screening scores than proficient readers [18].…”
Section: Discussionsupporting
confidence: 87%
“…Also, the percentage of children that get tired while reading, suffer from headaches, feel that their eyes cry or itch when they read, need to follow the text with their finger, or even get confused or miss words when reading, is lower in the group of children with good academic performance. These results are aligned with other studies carried out in different countries, such as that published by Jan et al, which concluded that better visual acuity is related to higher academic performance in a cohort of children aged between 11 and 16 in China [17]. Regarding reading, Goldstand et al demonstrated in 2006, in 71 seventh grade children, how nonproficient readers had significantly poorer academic performance and vision-screening scores than proficient readers [18].…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were reported in English learning performance [20]. A prospective cohort study showed that a better visual acuity in seventh grade was significantly associated with higher ninth-grade scores [21], which suggested an interfere with education potential from visual impairment. The adverse association between poor vision and academic performance may be due to the educational inequity caused by poor vision.…”
Section: Introductionsupporting
confidence: 80%
“…This latter finding is particularly relevant given that early literacy has been shown to be a key indicator of future reading and educational ability . In a prospective longitudinal study of Chinese middle school children (Grades 7 to 9), Jan et al observed a significant association between poorer habitual acuity of the better eye at the initial eye examination in Grade 7, and lower scores on a standardised academic test in Grade 9. In the latter study, presenting visual acuity included measures of unaided vision.…”
Section: Vision Refractive Error and Academic Performancementioning
confidence: 97%
“…While many studies have reported that habitual distance visual acuity is unrelated to academic ability, a number of studies have demonstrated a link between habitual visual acuity and reading or school performance . Direct comparisons between studies can be difficult due to inconsistencies in terminology, with some authors considering uncorrected vision to be a measure of visual acuity . Protocols or analyses also vary with respect to measures of monocular or binocular visual acuity, where some studies utilise data from the better eye only …”
Section: Vision Refractive Error and Academic Performancementioning
confidence: 99%